Risk factors for lymph node metastasis and surgical methods in patients with early-stage peripheral lung adenocarcinoma presenting as ground glass opacity - Yongming Wang (Journal of Cardiothoracic Surgery, 2020)
Abstract Background It is difficult to predict lymph node metastasis in patients with early lung cancer. Pure ground glass opacity (GGO) on computed tomography indicates an early-stage adenocarcinoma that can be removed by limited resection or lobectomy without the need for mediastinal lymph node dissection or sampling, and lung adenocarcinoma with GGO therefore has a good prognosis. We examined the incidence and risk factors of lymph node metastasis in patients with clinical stage IA lung adenocarcinoma. Methods We retrospectively analyzed clinical data for 327 patients with stage IA peripheral lung cancer treated in our hospital from March 2014 to December 2018. The patients were divided into four groups according to computed tomography signs. Lobectomy and systematic lymph node dissection were performed in all patients. Correlations between lymph node metastasis and clinical pathological factors were analyzed by logistic regression. Results Among the 327 patients, 26 (7.95%) had lymph node metastasis. No patients with pure GGO or GGO-dominant types had lymph node metastasis. Logistic regression identified tumor diameter, solid content, plasma carcinoembryonic antigen (CEA) level, pathological type, lymphovascular invasion, and pleural invasion as factors related to the presence of lymph node metastasis. Conclusions Tumor diameter, solid component ratio, plasma CEA level, pathological type, vascular tumor thrombus, and pleural invasion are possible independent risk factors for lymph node metastasis in patients with stage IA lung adenocarcinoma. In contrast, lymph node metastasis is rare in patients with pure GGO or GGO-dominant lung adenocarcinoma.